Effect of interest rate capping on capital market performance in Kenya - Thuo, Tabitha (Strathmore University, 2019)
The National Assembly of Kenya amended the Banking Act (2015) and introduced interest rate capping effective September 2016. This reopened an old debate over the appropriateness of regulatory interventions on bank interest rates. Proponents of interest rate capping argued that the credit market was inelastic and that interest rates were not being determined by market forces; resulting in banks charging high non-market interest rates on loans and paying low interest on deposits. In contrast, critics argued that interest rate caps would distort the market and prevent banks from offering loan products to borrowers at the lower end of the market who have no alternative access to credit. Informed by the close relation between financial and capital markets as well as the importance of the latter as an alternative source of business capital and investment asset class, this study sought to examine the effect of interest rate capping on the capital market performance in Kenya during the five years period from 2013 to 2018. The study used monthly secondary data from the Central Bank of Kenya and Nairobi Securities Exchange (NSE). Using panel data and event analysis, the study found that interest rates on loans and deposits had a significant negative effect on equity market performance; but insignificant positive effect on debt market performance. Interest rate capping on deposits had no significant effect on equity market performance while capping of interest rates on loans had a positive effect on equity market performance. Interest rate capping on loans and savings had no significant effect on debt market performance. Government borrowing was found to have a significant negative moderating effect on the relationship between interest rates and equity market performance. The study concluded that government borrowing increases interest rates and also reduces equity market performance. Further conclusion was that capping of interest rate on loans significantly improved equity market performance. The study recommends that the Central Bank should use market-based policies to influence interest rates since interest rate capping delivers desired effects in short term. Further, the government should focus on market interest rate stabilization to avoid the long run negative effects of interest rate capping on the economy. Further studies can examine the relationship between interest rate capping with equities at security level. Another study can determine the transmission mechanism of interest rate capping to the debt segment of capital markets.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Interest rate capping; Capital market; Performance_Kenya